2019
DOI: 10.1016/j.jpeds.2018.08.079
|View full text |Cite|
|
Sign up to set email alerts
|

Weaning of Moderately Preterm Infants from the Incubator to the Crib: A Randomized Clinical Trial

Abstract: Objective To assess whether length of hospital stay is decreased among moderately preterm infants weaned from incubator to crib at a lower vs higher weight. Study Design This trial was conducted in the Eunice Kennedy Shriver National Institute of Child Health and Human Development Neonatal Research Network. Infants with gestational ages 29–33 weeks, birthweight <1600 g, and in an incubator were randomly assigned to a weaning weight of 1600 or 1800 g. Within 60 to 100 g of weaning weight, the incubator temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…For instance, a review by Razak indicated that infants transferred to open cots at a weight lower than 1600 g gained more weight and grew better [9]. The adequacy of transferring infants to open cots at around 1500-2000 g has also been suggested in many studies [4,5,7,8,[10][11][12]. All the above evidence implies that weaning preterm neonates from incubators at different weight levels is feasible, based on their stable condition at the decision of weaning and a stage of dynamic equilibrium in changes of their physiological parameters (e.g., daily calorie changes and daily body weight changes).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, a review by Razak indicated that infants transferred to open cots at a weight lower than 1600 g gained more weight and grew better [9]. The adequacy of transferring infants to open cots at around 1500-2000 g has also been suggested in many studies [4,5,7,8,[10][11][12]. All the above evidence implies that weaning preterm neonates from incubators at different weight levels is feasible, based on their stable condition at the decision of weaning and a stage of dynamic equilibrium in changes of their physiological parameters (e.g., daily calorie changes and daily body weight changes).…”
Section: Discussionmentioning
confidence: 99%
“…As an indicator of maturity, the body weight status has widely been proven to reflect a neonates growth velocity and adaptation to its environments [ 6 ]. Further, it also serves as an important indicator of the following factors: successful weaning from the incubator to the crib [ 4 ], the length of hospital stays [ 7 , 8 ], and the discharge weight [ 4 , 7 ]. Therefore, most of the relevant research has compared weaning infants of different weight ranges to determine if there were any positive or negative effects of weight on weaning in these vulnerable neonates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,8,23 However these clinical markers can be modified with other resources, such as, for example, a heated cradle, antipyretic and blood pressure regulating medications, among others. [36][37][38][39] Rev Paul Pediatr. 2021;39:e2019399…”
Section: Discussionmentioning
confidence: 99%